2015
DOI: 10.1186/s12913-015-0825-0
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards the use and acceptance of eHealth technologies: a case study of older adults living with chronic pain and implications for rural healthcare

Abstract: BackgroundProviding health services to an ageing population is challenging, and in rural areas even more so. It is expensive to provide high quality services to small populations who are widely dispersed; staff and patients are often required to travel considerable distances to access services, and the economic downturn has created a climate where delivery costs are under constant review. There is potential for technology to overcome some of these problems by decreasing or ceasing the need for patients and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
136
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 18 publications
13
136
1
3
Order By: Relevance
“…Some DHT applications and web sites address this by including interactive components such as quizzes, case studies and informative pictures and videos that enhance learning and are updated regularly (Currie et al 2015, Algeo et al 2017) and these can encourage older people's engagement. Essery et al (2017) found that almost all users who completed a trial of the dizziness management website felt it offered new information and taught new skills, despite some of the users having already completed the same activity using a booklet-based format (Essery et al 2017).…”
Section: The Novelty Factormentioning
confidence: 99%
See 4 more Smart Citations
“…Some DHT applications and web sites address this by including interactive components such as quizzes, case studies and informative pictures and videos that enhance learning and are updated regularly (Currie et al 2015, Algeo et al 2017) and these can encourage older people's engagement. Essery et al (2017) found that almost all users who completed a trial of the dizziness management website felt it offered new information and taught new skills, despite some of the users having already completed the same activity using a booklet-based format (Essery et al 2017).…”
Section: The Novelty Factormentioning
confidence: 99%
“…However, poor internet connection was an ongoing barrier to DHT for older people living in rural locations due to slower download speeds and inability to use videoconferencing software. It is important to consider the appropriateness of DHT design that relies on webbased services when identifying potential users living outside urban areas (Currie et al 2015).…”
Section: Re-evaluating Ongoing Benefitmentioning
confidence: 99%
See 3 more Smart Citations